Teaching, curriculum, and community involvement - Hiatt-Michael, Diana B. (Family, school, community, partnership., 2008)
This publication features Hiatt-Michael's research and practice during thirty-four years as Professor of Education at the Graduate School of Education and Psychology, Pepperdine University. The chapters represent a range of her major thoughts on teaching, curriculum and family-community involvement by the author. Her work has broadened the scope and understanding of the commonalities of teaching and curriculum across disciplines and professional work. In addition, she has expanded the concept of the site-based school to include and engage the families and community as well as the students and professional staff. Lastly, she connects research and practice of schooling across continents, noting stages of development in educational practices.The forward presents personal insights to the author's professional growth. A chronological reading of the chapters will reveal the development of a faculty member from early researcher to award-winning author of theory-to-practice material in a given field of study.